Pulse pressure classes and clinical features of patients at the annual stage of medical therapy after permanent pacing - Pochynska, Maryna; Yabluchanskyi, Mykola (ScienceRise: Medical Science, 2017)
The aim of study was to assess the changes of patient’s clinical signs in pulse pressure classes at the annual stage after pacemaker implantation and drug therapy. Methods. It is included 220 patients at the annual stage of the drug therapy after pacemaker implantation divided in pulse pressure (PP) classes (I - very low PP - less than 20 mmHg, II - low more than 20 - less than 40 mmHg, III - the norm - 40 - 60 mmHg, IV - high more than 60 - less than 80 mmHg, very high PP - more than 80 mmHg). We evaluated the frequencies of occurrence of the postinfarction cardiosclerosis, functional classes (FC) of stable angina; stages and severity of arterial hypertension; diabetes mellitus, forms of atrial fibrillation; FC and stages of chronic heart failure (CHF). Student’s t-test was used. Results. It is necessary to strengthen antihypertensive therapy of patients with implanted pacemakers, especially in IV and V PP classes. Conclusion. At the annual stage after pacemaker implantation drug therapy helps to reduce the frequency of clinical signs of patients in low and high PP classes, accompanied by their concentration in III PP class